Human nasal mucosal C-reactive protein responses after inhalation of ultrafine welding fume particles: positive correlation to systemic C-reactive protein responses. Issue 10 (26th November 2018) - Baumann, R.; Brand, P.; Chaker, A.; Markert, A.; Rack, I.; Davatgarbenam, S.; Joraslafsky, S.; Gerhards, B.; Kraus, T.; Gube, M.
Abstract: Exposures to occupationally relevant ultrafine, zinc- and copper-containing welding fumes cause inflammatory responses involving systemic IL-6, C-reactive protein (CRP) and serum amyloid A (SAA), all associated with elevated risk of cardiovascular events. We investigated whether the systemic response is preceded by nasal inflammatory reactions. Fifteen nonsmoking male subjects were exposed for 6 h under controlled conditions to zinc-/copper-containing welding fumes (at 2.5 mg/m 3 ) or ambient air control in a randomized order. Nasal secretions were collected before and at 1, 3, 6, 10, and 29 h after exposure. Nasal levels of selected biomarkers were determined by electrochemiluminescent assays and related to their systemic levels. Nasal interferon-γ (IFN-γ) peaked significantly 1 h after start of exposure compared to baseline. Nasal CRP as well as SAA increased significantly at 10 and 29 h compared to baseline. Receiver operating characteristic (ROC) curve analysis for differentiating welding fume from control exposure was performed: The highest area under ROC curve (AUC) values were found for the CRP increases (10, 29 h versus 0 h): AUC = 0.83, and for IFN-γ increases (1 h versus 0 h): AUC = 0.92. Nasal and systemic changes of CRP at 29 h revealed a strong correlation (Spearman rank test: increases compared to baseline: r = 0.815, p = 0.0022; absolute levels: r = 0.9, p = 0.0002). In conclusion, short-term exposure to a zinc- and copper-containing welding fume causes significant increases of inflammatory mediators in nasal mucosal lining fluid. Therefore, measurement of nasal inflammatory mediators may provide a useful means for occupational surveillance of workers exposed to ultrafine metal fume particles.